Effect of storage temperatures and duration on quality of prepared chicken breast with paprika oleoresin. (18th December 2018) - Lu, Qing; Sun, Jingxin; Huang, Ming; Guo, Yuchen; Memon, Arif
Abstract: The objective of this study was to investigate the effect of storage temperatures and time on discoloration and oxidation of prepared chicken breast with paprika oleoresin. Freshly prepared chicken breast containing paprika oleoresin was stored at −2, −10, −18°C, and an oscillating temperature between −10 and −18°C (−10/−18°C). A significant decrease in redness was detected at −2, −10, and −10/−18°C. The lowest TBARS values and carbonyl contents were observed in the samples stored at −18°C for 5 weeks. Also, the values of sulfhydryl groups gradually decreased with the increase in storage temperatures and duration. The results suggest a positive correlation between the loss of redness and oxidation in all samples. The findings indicated that the discoloration and oxidation of prepared chicken breast added with paprika oleoresin were inhibited significantly when stored at −18°C.